Pengembangan Aplikasi Pendeteksian Kecurangan dalam Ujian Daring menggunakan Konsep Context Aware pada Platform Android - Alfredo Juan Pratama; Agi Putra Kharisma; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
In learning and teaching practice, a way to assess one's achievement in studies is needed. Method that is usually used is test or exam, which is a scoring method using sets of question and command that needed to be fulfilled. Medium for examination keeps evolving, from paper (CBT), computer (CBT), and mobile based (MBA). Computerized examination makes the exam itself doesn't need to be held in one place by using online examination method. Online examination uses multiple choice method to make exam scoring easier, but it's also more vulnerable to cheating attempt than essay. Due to the large number of mobile device users with the Android operating system and its capabilities that have many sensors, the author offers a solution, namely an Android-based context aware online exam application. Application uses light sensor, gyroscope sensor, microphone, and GPS to get light intensity data, sound decibels, device orientation, and user's location to detect cheating attempt. Application tested using black box, compatibility testing, and usability testing. The result of black box testing is 100% valid, result of compatibility testing is 100% for Android 7.0 until 10.0, and the result of usability testing score is 70.5 which is categorized as acceptable.